Environmental Risks - Mihai, Florin-Constantin; Grozavu, Adrian (IntechOpen, 2018)
Environmental risks are a multi- and interdisciplinary topic with a great interest in current society. This book examines the issues of natural hazards (e.g., typhoons, landslides, wildfires), anthropogenic activities (construction of artificial dams, the operation of nuclear power plants), and their potential risks to the environment and/or quality of life at various scales, from local to regional and even at a global level. The book intends to discuss concepts, methods, and techniques to address environmental risks and vulnerabilities, revealing the complex interactions between nature and human communities and activities. Policies and practices for disaster risk management should be based on the best state-of-the-art methods and techniques, integration between natural and/or social approaches, interdisciplinary research, and multilevel cooperation.